العوامل المؤثرة على الثقافة الصحية لذوي الاحتياجات الخاصة الممارسين لأوجه النشاط الرياضي - شناتي ناجي; Supervisor زواق أمحمد (Mohamed Boudiaf University of M'sila, 2024)
الملخص: بالعربية (عبارة عن فقرة: ( تناولت هذه المذكرة موضوع تأثير ممارسة الرياضة على الصحة النفسية. تم عرض الدراسات والأبحاث التي تُظهر تأثير الرياضة الإيجابي على الصحة النفسية، مثل تحسين المزاج، وتقليل القلق والتوتر، وزيادة الثقة بالنفس، وتحسين جودة النوم. تم تقديم توصيات في نهاية المذكرة بأهمية ممارسة الرياضة بانتظام، ونشر الوعي حول فوائدها على الصحة النفسية عنوان الدراسة: العوامل المؤثرة على الثقافة الصحية لذوي الاحتياجات الخاصة الممارسين لأوجه النشاط الرياضي. أهداف الدراسة: الهدف الرئيسي لهذه الدراسة هو فهم العلاقة بين النشاط الرياضي والثقافة الصحية لذوي الاحتياجات الخاصة. يتضمن ذلك فهم كيف يمكن للنشاط الرياضي تحسين الصحة البدنية والعقلية، وتعزيز الثقة بالنفس، وتحسين المهارات الاجتماعية. كما تهدف الدراسة إلى استكشاف العوامل الأخرى التي قد تؤثر على الثقافة الصحية لذوي الاحتياجات الخاصة الممارسين للنشاط الرياضي، مثل الوصول إلى المرافق الرياضية المناسبة، والدعم الاجتماعي، والتعليم الصحي مشكلة الدراسة: تعتبر الثقافة الصحية لذوي الاحتياجات الخاصة الممارسين لأنشطة رياضية موضوعًا معقدًا وشاملًا يتطلب دراسة متعمقة ومتعددة الجوانب . فرضيات الدراسة: • هناك فرق ذو دلالة إحصائية بين مستوى ممارسة الرياضة لدى ذوي الاحتياجات الخاصة في مدينة مسيلة حسب النوع. • هناك فرق ذو دلالة إحصائية بين مستوى الصحة النفسية لدى ذوي الاحتياجات الخاصة في مدينة مسيلة حسب مستوى ممارسة الرياضة. • ممارسة الرياضة تساهم في تحسين الصحة النفسية وتقليل مستويات القلق والاكتئاب. • المشاركة في الأنشطة الرياضية تساهم في رفع مستوى التقدير الذاتي لدى ذوي الاحتياجات الخاصة المنهج المتبع في الدراسة: ا لوصفي التحليلي الأدوات المستخدمة في الدراسة الاستبيانات , المقابلات الشخصية, برنامج SPSS كلمات المفتاحية : ممارسة الرياضة، الصحة النفسية، ذوي الاحتياجات الخاصة، الثقافة الصحية، النشاط البدني، الدعم الاجتماعي، التكيف البيئي . بالإنجليزية Keywords : Physical Exercise, Mental Health, Special Needs Individuals, Health Culture, Physical Activity, Social Support, Environmental Adaptation جاء هذا البحث في فصول: الفصل الأول: الإطار العام للدراسة بما في ذلك الإشكالية، التساؤلات الفرعية، الفرضيات، الأهداف وأهمية الدراسة، واستعراض الدراسات السابقة ذات الصلة. الفصل الثاني: الخصائص الفردية المؤثرة على الثقافة الصحية، مثل العمر والجنس والمستوى التعليمي. الفصل الثالث: العوامل الخارجية المؤثرة على الثقافة الصحية، مثل البيئة الاقتصادية والاجتماعية والإعلامية. الفصل الرابع: منهجية الدراسة، متضمنة الدراسة الاستطلاعية، المنهج المستخدم، متغيرات الدراسة، وأساليب جمع وتحليل البيانات. من أهم النتائج التي توصل إليها الباحث: ● ممارسة الرياضة بانتظام تؤدي إلى تحسين الصحة النفسية وتقليل مستويات القلق والاكتئاب. ● توجد فروق ذات دلالة إحصائية بين مستوى الصحة النفسية لدى ذوي الاحتياجات الخاصة تبعًا لمستوى ممارسة الرياضة. توصل الباحث للعديد من التوصيات أهمها: ● تشجيع ذوي الاحتياجات الخاصة على ممارسة الرياضة بانتظام. ● توفير المرافق والتجهيزات الملائمة لممارسة الرياضة. ● تعزيز الوعي بأهمية ممارسة الرياضة للصحة النفسية من خلال حملات توعية وبرامج إعلامية. كشاف بالانجليزية Faculty: Institute of Sciences and Techniques of Physical and Sports Activities Department: Order Number:……………………………………………………………………………… Registration Number: UN280120232302486593 Researcher : CHENATI NADJI Publicly Defended on: June 5, 2024, from 8:00 AM to 9:30 AM Thesis Title: The factors influencing health culture among individuals with special needs practicing sports activities Thesis Language: Arabic Thesis Model: Country: REPUBLIC OF ALGERIA-M’SILA University: University of M’sila Supervisor's Name: Dr. Zewak Amhamed Rank: Lecturer Number of Pages: 79 (Cd-Rom Word * PDF) Electronic File* Specialty: Adapted Physical Activity and Health Option: ........................... Abstract: This study examines the factors influencing the health culture among individuals with special needs practicing sports activities. It highlights the positive effects of sports on mental health, such as mood improvement, reduced anxiety and stress, increased self-confidence, and improved sleep quality. The study also provides recommendations for promoting regular sports activities and raising awareness about their benefits for mental health. The aim of the study: Understanding the relationship between sports activities and health culture among individuals with special needs, and exploring other factors that might influence their health culture. Problem Statement: Understanding the complex and multifaceted health culture of individuals with special needs practicing sports, influenced by social, physical, and mental factors. Hypotheses: 1. Regular sports activities enhance physical and mental health culture among individuals with special needs. 2. Social support and a healthy environment positively influence the practice of sports activities. 3. There is a significant difference in the level of sports activities among individuals with special needs in M'sila based on gender. 4. There is a significant difference in mental health levels among individuals with special needs in M'sila based on the level of sports activities. 5. Regular sports activities help reduce anxiety and depression levels. 6. Participation in sports activities increases self-esteem levels among individuals with special needs. Keywords: Physical Exercise, Mental Health, Special Needs Individuals, Health Culture, Physical Activity, Social Support, Environmental Adaptation The most important results achieved are: ● Regular sports activities improve mental health and reduce anxiety and depression levels. ● There are significant differences in mental health levels based on the frequency of sports activities. ● Regular sports participation enhances self-esteem among individuals with special needs. ● Environmental and social support are crucial in promoting regular sports activities among individuals with special needs.
Keywords: ممارسة الرياضة; الصحة النفسية; ذوي الاحتياجات الخاصة; الثقافة الصحية